Analisis Lifetime Dan Kerusakan Rear Leaf Spring Truk Iveco AD 410 Untuk Meningkatkan Ketepatan Perencanaan Penggantian - Muhammad Imam Yusuf; Braam Delfian Prihadianto (P3M Politeknik Negeri Cilacap, 2022)
Components in a unit have a certain lifetime, therefore maintenance and rejuvenation are needed to maintain performance, including leaf springs. The rear leaf spring component replacement of the Iveco AD 410 truck unit in the MIFA Project was not conducted as scheduled. The purpose of this study is to improve the planning accuracy of the rear leaf spring component replacement for the Iveco AD 410 truck on the MIFA Project. The methods used in this study were qualitative and comparative quantitative method and also reliability centered spares using the normal distribution processing method. The test data used were work order data for 2018-2020 and replacement recommendation data from the manufacturer. The results of the analysis of this study indicate that the average lifetime of the rear leaf spring component is shorter than the recommended lifetime from the manufacturer with 18% decrease in component efficiency. This is caused by extreme road conditions and the lack of maximum maintenance on the leaf spring components.